PSYCHOLOGICAL TRAUMA IN WOMEN AND ITS SOCIAL REHABILITATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
It is well known that psychological stress and trauma in a person is a reality that we encounter in our social life. In recent years, around the world the scale of women who are under the pressure and at the result of it, go through post-traumatic stress disorder have increased. This scientific article analyzes the psychological complications and rehabilitation of post-traumatic stress disorder in women. Factors such as the role of women in society, their socio-psychological characteristics, the manifestation of moral qualities and the specificity of character traits are also studied.